Age-related hearing loss: An updated and comprehensive review of the interventions - Elham Tavanai; Vida Rahimi; Mohammad Ehsan Khalili; Somayeh Falahzadeh; Masoud Motasaddi Zarandy; Ghassem Mohammadkhani (Iranian Journal of Basic Medical Sciences, 2024)
Aging causes progressive degenerative changes in many organs, particularly the auditory system. Several attempts have been conducted to investigate preventive and therapeutic strategy/strategies for age-related auditory dysfunction, such as maintaining a healthy lifestyle through good nutrition, lower anxiety levels, and noise exposure, different pharmacological approaches, gene and cell therapy, and other strategies. However, it is not clear which approach is the best to slow down these dysfunctions because several different underlying mechanistic pathways are associated with presbycusis which eventually leads to different types of this disease. A combination of several methods is probably required, whereas the effectiveness for some people needs to be monitored. The effectiveness of treatments will not be the same for all; therefore, we may need to have a unique and personalized approach to the prevention and treatment of ARHL for each person. In addition, each method needs to specify what type of presbycusis can prevent or treat and provide complete information about the extent, duration of treatment, persistency of treatment, side effects, and whether the approach is for treatment or prevention or even both. This paper reviews the updated literature, which targets current interventions for age-related hearing loss.